Radio Frequency Integrated Circuit Design for Cognitive Radio Systems - Fahim, Amr (Springer International Publishing : Imprint: Springer, 2015)
This book fills a disconnect in the literature between Cognitive Radio systems and a detailed account of the circuit implementation and architectures required to implement such systems.  Throughout the book, requirements and constraints imposed by cognitive radio systems are emphasized when discussing the circuit implementation details.  In addition, this book details several novel concepts that advance state-of-the-art cognitive radio systems.  This is a valuable reference for anybody with background in analog and radio frequency (RF) integrated circuit design, needing to learn more about integrated circuits requirements and implementation for cognitive radio systems. ·         Describes in detail cognitive radio systems, as well as the circuit implementation and architectures required to implement them; ·         Serves as an excellent reference to state-of-the-art wideband transceiver design; ·         Emphasizes practical requirements and constraints imposed by cognitive radio systems, when discussing circuit implementation details.  .